2014
DOI: 10.1111/ijsw.12080
|View full text |Cite
|
Sign up to set email alerts
|

Nonformal education for improving educational outcomes for street children and street youth in developing countries: A systematic review

Abstract: formal education for improving educational outcomes for street children and street youth in developing countries: A systematic review Tens of millions of children and youth (up to 24 years of age) live and work on the streets of developing countries. Most of them are forced to leave formal education. As a potential solution, nonformal education (NFE) interventions have spread worldwide. However, no previous attempt has been made to address the state of evidence regarding effectiveness studies of NFE for street… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Seven papers examined potential occupation-based practices with street children in developing countries (e.g., D. Shephard, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven papers examined potential occupation-based practices with street children in developing countries (e.g., D. Shephard, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Seven papers examined potential occupation-based practices with street children in developing countries (e.g., D. Shephard, 2014). Interventions include the use of play; storytelling; engagement in peer-led dialogue around occupational goals; academic, pre-vocational, and life skills training; stimulation programs; and social enterprises for adolescents.…”
Section: Current Occupation-based Practicesmentioning
confidence: 99%
“…Several previous studies related to the issue of children in street situations discussed more on the aspects of knowledge, education, economy, and health. For example, research conducted by (Shephard, 2014) attention (Obregón & Tufte, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Berckmans 2013 focused on services provided in LMICs and included qualitative literature similar to our thematic synthesis of engagement‐related factors discussed in LMIC qualitative literature (Coren 2014; Coren 2015). We searched a recent systematic review of non‐formal education for street‐connected children and youth (Shephard 2014) to find studies eligible for our review, but we identified none.…”
Section: Introductionmentioning
confidence: 99%